Social information retrieval systems emerging technologies and applications for searching the Web effectively - Goh, Dion; Foo, Schubert (Hershey, Pennsylvania Information Science Reference, 2008)
"Provides relevant content in the areas of information retrieval systems, services, and research; covering topics such as social tagging, collaborative querying, social network analysis, subjective relevance judgments, and collaborative filtering. Answering the increasing demand for authoritative resources on Internet technologies, this will make an indispensable addition to any library collection"--Provided by publisher.
Collaborating to search effectively in different searcher modes through cues and specialty search / Naresh Kumar Agarwal and Danny C.C. Poo -- Collaborative querying using a hybrid content and results-based approach / Chandrani Sinha Ray ... [et al.] -- Collaborative classification for group-oriented organization of search results / Keiichi Nakata and Amrish Singh -- A case study of use-centered descriptions : archival descriptions of what can be done with a collection / Richard Butterworth -- Metadata for social recommendations : storing, sharing, and reusing evaluations of learning resources / Riina Vuorikari, Nikos Manouselis, and Erik Duval -- Social network models for enhancing reference-based search engine rankings / Nikolaos Korfiatis ... [et al.] -- From PageRank to social rank : authority-based retrieval in social information spaces / Sebastian Marius Kirsch ... [et al.] -- Adaptive peer-to-peer social networks for distributed content-based Web search / Le-Shin Wu ... [et al.] -- The ethics of social information retrieval / Brendan Luyt and Chu Keong Lee -- The social context of knowledge / Daniel Memmi -- Social information seeking in digital libraries / George Buchanan and Annika Hinze -- Relevant intra-actions in networked environments / Theresa Dirndorfer Anderson -- Publication and citation analysis as a tool for information retrieval / Ronald Rousseau -- Personalized information retrieval in a semantic-based learning environment / Antonella Carbonaro and Rodolfo Ferrini -- Multi-agent tourism system (MATS) / Soe Yu Maw and Myo-Myo Naing -- Hybrid recommendation systems : a case study on the movies domain / Konstantinos Markellos ... [et al.].
Electronic reproduction.
Keywords: Internet searching; Web search engines; World Wide Web -- Subject access; Information storage and retrieval systems; Information retrieval; Electronic books